Effective Language Teaching and Learning Model for Speaking English at Kampung Inggris PALI - Y. D. Fitriansyah; M. Taslim; R. L. Gaol; I. Wati; T. Rahmania; R. Rusmiana (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
English Language Teaching and Learning Model is very essential to improve Students’ English skill. Kampung Inggris PALI has shown effectiveness to improve students’ English speaking skill. Most of the activities both inside and outside of the classroom support the students’ English Speaking Skill, such as repeating word-phrase, simple short question-answer, translation, simple dictation, Sentence Drilling, and English speaking games. Students learn English with high motivation, with higher extrinsic motivation than intrinsic motivation. As the first issue, the owner and tutor of Kampung Inggris PALI has no information about what model of English Teaching and Learning they use effectively not only to gain but also to improve English Speaking Skill, luckily the tutors manage a well-managed role as a teacher to support the speaking activities. The second issue is the class have been attended by various of age, though they provide at least three different category of class: Young Learner Class, Adolescent Learner Class, and Adult Learner Class. The third issue is there is no formal and written lesson plan with the support of a written syllabus for all classes. Last, the fourth issue is to give a more cultural context and job requirement context as the content of English Language Teaching and Learning Model